Study of congenital Morgagnian cataracts in Holstein calves - Braun, Marina (PLoS One, 2019)
Cataracts are focal to diffuse opacities of the eye lens causing impaired vision or complete blindness. For bilateral congenital cataracts in Red Holsteins a perfectly cosegregating mutation within the CPAMD8 gene (CPAMD8:g.5995966C>T) has been reported. We genotyped the CPAMD8:g.5995966C>T variant in Holstein calves affected by congenital bilateral congenital cataracts, their unaffected relatives and randomly selected herd mates. Ophthalmological examinations were performed in all affected individuals to confirm a congenital cataract. Whole genome sequencing was employed to screen variants in candidate genes for the Morgagnian cataract phenotype. In the present study, 3/35 cases were confirmed as homozygous mutated and 6/14 obligate carriers. Further 7/46 unaffected animals related with these cases were heterozygous mutated for the CPAMD8:g.5995966C>T variant. However 32 cases with a congenital cataract showed the wild type for the CPAMD8 variant. We did not identify variants in the candidate genes CPAMD8 and NID1 or in their close neighborhood as strongly associated with the congenital cataract phenotype in Holstein calves with the CPAMD8 wild type. In conclusion, the CPAMD8:g.5995966C>T variant is insufficient to explain the majority of Morgagnian congenital cataract phenotypes in Holsteins. It is very likely that congenital bilateral cataracts may be genetically heterogeneous and not yet known variants in genes other than CPAMD8 and NID1 are involved.